Development of E-Modules Based on Ethnomathematics of Anjuk Ladang Batik Motifs Assisted by GeoGebra - Brilian Rahma Fitria; Rini Setianingsih (MATHEdunesa, 2026)
The use of textbooks in the learning process tends to make learning less motivating for students. This is because textbooks primarily focus on delivering content without considering students' motivation and engagement. In addition, the integration of technology in schools remains relatively low. Therefore, an interactive e-module based on the ethnomathematics of Batik Anjuk Ladang and supported by GeoGebra was developed. The e-module serves as an alternative learning resource that promotes interactive learning. The integration of Batik Anjuk Ladang’s ethnomathematics provides contextual content to help enhance students’ self-learning motivation, while GeoGebra is used to offer visualization and increase the interactivity of the e module. This e-module was developed using the Plomp development model, which consists of three phases: preliminary research, development or prototyping, and assessment. The e-module focuses on Grade IX junior high school geometry transformation material and was developed using Flip PDF Professional and GeoGebra. The module was tested at SMP Negeri 2 Nganjuk with a group of Grade IX students. The quality of the developed e-module was evaluated based on validity, practicality, and effectiveness criteria. The study produced a detailed description of the e-module development process. The average material validity score was 86.31%, categorized as very valid— especially in terms of user-friendliness. The media validity score was 86.08%, also very valid with the same dominant criterion. The practicality score reached 85.09%, classified as very practical, with multimedia clarity as the most prominent aspect. The effectiveness of the e-module was demonstrated by an average N-gain score of 0.701, indicating a high category. Therefore, the developed e-module meets the criteria of being valid, practical, and effective for facilitating independent learning in geometry transformation.